Transport properties of single TiO2 nanotubes - Stiller, Markus; Barzola-Quiquia, Jose; Lorite, Israel; Esquinazi, Pablo; Kirchgeorg, Robin; Albu, Sergiu; Schmuki, Patrik (Applied Physics Letters, 2013)
We investigated the electric transport properties of single TiO2 nanotubes separated from an anodic titania nanotube array. The temperature dependence of the resistance measured with the conventional four point method of all investigated samples show a Mott variable range hopping behavior. The results obtained with two contacts indicate the existence of a potential barrier between the Cr/Au contacts and samples surfaces, which influence is clearly observable at temperatures <150 K. Impedance spectroscopy in the frequency range of 40 Hz to 1 MHz carried out at room temperature indicates that the electronic transport of these polycrystalline tubes is dominated by the grain cores.
EAM Import::2019-03-13